A new species of lac insect in the genus Kerria Targioni Tozzetti (Hemiptera: Coccomorpha: Tachardiidae) on Samanea saman (Fabaceae) from India - Rajgopal, N. N.; Mohanasundaram, Arumugam; Sharma, Kewal Krishan (Zootaxa, 2021)
A new species of lac insect (Hemiptera: Coccomorpha: Tachardiidae), Kerria canalis Rajgopal sp. nov., collected from Rain Tree, Samanea saman (Jacq.) Merr. (Fabaceae), from India (Tamil Nadu, Madurai), is described and illustrated. Detailed line diagrams and photographs, and a key for the identification of all known Kerria species are provided. Variations in the taxonomic characters of K. canalis and its congeners are discussed.